Efeito antioxidante da bactéria Herbaspirillum seropedicae associada a genótipo de trigo submetido ao déficit hídrico e fertilização nitrogenada - Hendges, Flávia Bordignon (2015)
Plants are constantly exposed to a variety of environmental stresses which cause reductions in productivity. Plants subjected to water stress undergo changes in the biochemical structure of your cells, including the production of reactive oxygen species (ROS) or free radicals and the plant in response to these free radicals, synthesize antioxidants. The objective of this study was to evaluate the antioxidant effect of inoculation with Herbaspirillum seropedicae bacteria associated with the wheat genotypes CD 120 submitted to drought and nitrogen fertilization. They were assessed physiological parameters such as membrane stability index (IEM), relative water content (RWA), fresh and dry biomass and enzymatic activity of antioxidant enzymes: catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and Glutathione S-transferase (GST), and proline contents and lipid peroxidation (MDA). The design was completely randomized in 4x2 factorial design with three replications, the first factor relates to the conditions of inoculation / fertilization (C0: control, C1: fertilization with ammonium sulfate, C2: inoculation with bacteria and C3: fertilization combined with inoculation) and the second factor relates to the water conditions with or without stress (at booting stage of the plants were submitted to water deficit for 8 days while the control plants were still being irrigated usually). Plants inoculated with H. seropedicae subjected to drought stress, show lower increases in IEM (19%) in the MDA (41%) and proline (6.7 times) compared with the control (30%, 70% and 25 times, respectively). Regarding the antioxidant effect, the drought caused greater reduction in specific activity of CAT regardless of fertilization conditions / applied inoculation. For SOD stressed plants and in the presence of bacteria, the levels of enzyme increased, and GST, the effect was reversed. However, the activity of APX remained unchanged, both the application of stress as the presence of inoculation. Bacterial presence increased the fresh and dry biomass and weight of 100 grains. Although little antioxidant effect observed there was no damage to the tissue and had no effect on yield under water stress conditions, yet the antioxidant effect, this was not capable of restoring